What do young people think about screening for cystic fibrosis?. Issue 5 (May 1991) - Cobb, E; Holloway, S; Elton, R; Raeburn, J A
Abstract : We investigated the knowledge of cystic fibrosis and the views about neonatal and carrier screening in 216 school students aged 14 to 16 years. This work was completed before the published identification of the cystic fibrosis gene in September 1989. Although initial knowledge of cystic fibrosis was low (only 17% of the students knew that the disease affected the lungs), there was good recall of basic information about cystic fibrosis and of recessive inheritance after a brief lecture. A total of 86% considered that carrier detection should be offered routinely and 88% felt that an offer of prenatal diagnosis for cystic fibrosis should be made if both prospective parents were known to be carriers. We believe that pilot studies of cystic fibrosis carrier screening in schools should be undertaken.